Mammary Branching Morphogenesis Requires Reciprocal Signaling by Heparanase and MMP‐14. Issue 8 (August 2015) - Gomes, Angélica Maciel; Bhat, Ramray; Correia, Ana Luísa; Mott, Joni D.; Ilan, Neta; Vlodavsky, Israel; Pavão, Mauro S.G.; Bissell, Mina
ABSTRACT The development of the mammary gland involves formation of a branched arboreal structure resulting from the penetration and proliferation of epithelial cells into the fat pad. The mammary cells invade by remodeling their surrounding extracellular matrix (ECM), which are rich in proteins, and glycans such as heparan sulfate proteoglycans (HSPGs). There is increasing literature on how the interaction between signaling by ECM and matrix metalloproteinases (MMPs) is relevant to morphogenetic and physiological contexts. Here we sought to understand how heparanase, the sole mammalian heparan sulfate‐degrading endoglycosidase may regulate mammary gland development. We found a robust localization of heparanase within growing end buds during branching in vivo. Using three‐dimensional (3D) organotypic cultures, we showed that heparanase expression and activity are required for mammary epithelial invasion/branching within dense collagen I gels. Morphometric analysis of glands from both heparanase‐overexpressing and knockout mice showed a direct correlation between degree of branching and the heparanase levels, confirming our 3D organotypic culture observations. Finally, we uncovered a reciprocal association between levels of heparanase and MMP14, a membrane‐bound MMP, shedding further light on how branching occurs within developing mammary glands. J. Cell. Biochem. 116: 1668–1679, 2015. © 2015 Wiley Periodicals, Inc.